Beef cattle data analytics: trends in feedlot cattle health, performance, and carcass traits, and effects of beef on dairy programs - McCabe, Esther Dorice (Kansas State University, 2021)
Data science has emerged as an academic field and an important decision-making tool for the private sector. This is the result of advances in technology that allow the collection and management of large data sets. Data analytics allows scientists to pursue questions that cannot be addressed with controlled experiments. The objective of studies within this dissertation was to use data analytics to evaluate trends in performance, health and carcass traits from feedlot cattle, and determine the effect of Holstein and beef-dairy cross breed descriptions of cattle lots on sale price. The first study utilized the Tri-County Steer Carcass Futurity Cooperative data collected from 2002 through 2018 to analyze trends across years for performance, health, and carcass traits for steers and heifers. Performance traits evaluated included arrival weight, average daily gain, feed to gain, days on feed, and harvest weight. The regression coefficients (slope) were significant (P < 0.10) for each of these traits for both steers and heifers with the exception of feed:gain (P = 0.59). The R² for these equations was small, however, indicating that year only accounted for small amount of the variation, and that there was little change in these traits for the duration of the study. Health trends included morbidity risk, number of times treated, and mortality risk. The percentage morbidity increased (P < 0.0001) for steers and heifers. The overall mean morbidity risk for steers was 24% and 20% for heifers. The percentage of steers and heifers receiving no treatments for morbidity decreased (P < 0.0001). Concurrently, the percentage of steers and heifers treated one, two, or three or more times increased (P < 0.0001). Mortality percentage increased for steers (P < 0.0001) and heifers (P < 0.001). The overall mean mortality risk for steers was 1.8% and 1.4% for heifers. Carcass trait trends evaluated included hot carcass weight, fat thickness, ribeye area, kidney pelvic heart fat percentage, dressing percentage, marbling score, calculated yield grade, and carcass value. The regression coefficients (slope) were significant (P < 0.01) for each of these traits for both steers and heifers. With the exception of carcass value, the R² value for these equations was small. This indicates that year only accounted for small amount of the variation, and that there was little change in these traits over the duration of the study. The second study utilized the Tri-County Steer Carcass Futurity Cooperative data to evaluate the effect of sire breed on performance, health, and carcass traits for steers and heifers. Sire breeds included in these analyses were Angus, Charolais, Hereford, Red Angus, and Simmental. Sire breed affected arrival weight, average daily gain, harvest weight, days on feed, feed to gain, feed cost, feed consumed, hot carcass weight, dressing percentage, fat thickness, ribeye area, calculated yield grade, and overall carcass value. Odds ratios were calculated for morbidity and mortality events. The sire breed of an animal was associated (P < 0.0001) with the likelihood of a morbidity event. Sire breed was not associated (P = 0.67) with mortality. The third study utilized Superior Livestock Auction data to determine 1) the relative value of Holstein feeder steer lots compared to the steer lots of other breed descriptions, and 2) value of beef-dairy crosses compared to other breed combinations on the sale price of lots of calves. Holstein feeder steer lots sold for the lowest (P < 0.05) sale price compared with all other breed descriptions. To determine potential change in relative value of Holstein feeder steers from 2010 to 2018, data were analyzed in three-year increments. In all three-year increments, Holstein feeder lots sold for the lowest (P < 0.05) sale price compared to the other breed descriptions of beef steer lots. There was a greater relative price discount in each year increment, likely indicating lessening interest in the feedlot sector to feed Holstein steers to harvest. As the value of the Holstein steer has decreased in the beef industry, some dairy producers are breeding lower performing dairy cows to beef semen, producing a beef-dairy cross animal. The second objective was to evaluate the value of beef-dairy cross lots compared with other breed descriptions of lots selling through summer 2020 video auctions. Beef-dairy cross calf lots sold for a greater (P < 0.05) sale price than Holstein lots. Beef-dairy cross lots sold for a lower (P < 0.05) sale price than Brahman influenced calf lots, English-Continental cross calf lots, and English, English cross calf lots. These results indicate the beef-dairy cross had greater value than the traditional Holstein calf entering the beef supply chain.
Keywords: Beef-dairy; Data analytics; Heifers; Holstein steers; Multiple regression; Odds ratio